Disaggregated data making sure that excluded people are included (The experience of the Las Piñas Persons with Disability Federation, Inc. in participatory data profiling) - Muego, Paul Edward N. (Philippine Journal of Social Development, 2019)
Addressing disability is a fundamental aspect of re-imagining social development and reclaiming people's development.An essential aspect of this is having disability-related data which can be used in measuring and tracking the progress of global development initiatives such as the Sustainable Development Goals as well as in deciding priorities, crafting policies, and developing and implementing development programs at the national and local levels. This article aims to describe the experiences of the Las Piñas Persons with Disability Federation, Inc. (LPPWDFI), an organization of persons with disabilities in developing, implementing, monitoring, and evaluating their own data-profiling project. This article utilized a combination of three methods: (a) Pakikiisa at Pakikipamuhay (Integration), (b) Kwentuhan at sama-aralan (Conversations, dialogue, reflection, and learning sessions) and (c) Pagbabasa at pagsusuri ng mga kwento at dokumento (Review and analysis of existing documents) with the underlying intent of listening to and valuing the perspectives and voices of persons with disabilities. Four critical factors that contributed to the success of the LPPWDFI's collective initiative are also discussed in the article: (a) Rights, identities, and aspirations of persons with disabilities, (b) Leadership development, capacity-building, and local initiatives, (c) The role of support organizations and the state, and (d) Facing the need to build on local gains. The article hopes that the story of LPPWDFI's data profiling initiative can open up spaces for introspection among organizations of persons with disabilities and eventually for their collective action aimed at creating inclusive communities in a more inclusive world.